2008
DOI: 10.1094/mpmi-21-1-0122
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Two Contrasting Genotypes of Rice to Brown Planthopper

Abstract: Rice (Oryza sativa L.) and brown planthoppers (BPH) (Nilaparvata lugens Stål) provide an ideal system for studying molecular mechanisms involved in the interactions between plants and phloem-feeding insects. The phenotypic responses and changes in transcript profiles of seedlings representing two rice cultivars differing in resistance to the BPH were analyzed. In the BPH-compatible (susceptible) cv. MH63, BPH feeding reduced three examined plant growth parameters (leaf area expansion, height increases, and dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
60
0
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 56 publications
4
60
0
7
Order By: Relevance
“…There is now considerable evidence to suggest that induced defenses are effective and have low fitness costs. Several studies have revealed that gene expression profiles in rice are reorganized in response to BPH feeding Yuan et al, 2005;Park et al, 2007;Wang et al, 2008). Such reorganization has been well documented in other plant-herbivore systems, supporting the hypothesis that inducible defenses contribute to rice resistance to the BPH.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…There is now considerable evidence to suggest that induced defenses are effective and have low fitness costs. Several studies have revealed that gene expression profiles in rice are reorganized in response to BPH feeding Yuan et al, 2005;Park et al, 2007;Wang et al, 2008). Such reorganization has been well documented in other plant-herbivore systems, supporting the hypothesis that inducible defenses contribute to rice resistance to the BPH.…”
Section: Discussionmentioning
confidence: 70%
“…In contrast, the expression of genes related to the flavonoid pathway, aromatic metabolism, and the octadecanoid pathway are mostly unchanged or down-regulated. This indicates that BPH feeding induces plant responses associated with a JA-independent pathway and cross talk with responses related to abiotic stress, pathogen invasion, and phytohormone signaling pathways Wang et al, 2005Wang et al, , 2008Yuan et al, 2005). Many studies have reported the effects of BPH feeding on physiological properties and metabolic changes in rice plants (Cagampang et al, 1974;Qiu et al, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Gene expression profiles in response to BPH infestation have been analyzed by several groups; however the mechanism of BPH resistance remains unclear (Wang et al 2008. In our microarray analyses, the gene expression levels of most JA/SA synthesis-or signaling-related genes in resistant lines .…”
Section: Discussionmentioning
confidence: 99%
“…The success of MAS such as Bph17 marker depends on several factors, including genetic base of trait, degree of association between molecular marker and target gene, number of individuals analyzed, and genetic background of the target gene to be transferred (Francia et al 2005;Wang et al 2008). DNA markers such as Bph17 need to be evaluated for identifying BPH biotypes.…”
Section: Introductionmentioning
confidence: 99%